Development of Mathematics Learning Media on Build Flat Side Space Using Smart Apps Creator - Tesalonika M. Oroh; Murni Sulistyaningsih; Derel F. Kaunang (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Learning mathematics in the subject of Build Flat-Side Space remains a challenge for junior high school students due to limited visual representation and minimal use of technological media that can facilitate spatial understanding. The abstract nature of shape concepts requires clear visualization, but conventional learning practices tend to rely only on static images in textbooks. This condition has an impact on the low level of concept understanding and learning motivation of students. Smart Apps Creator (SAC) as an interactive media development tool has the potential to provide dynamic visualizations and a more interesting learning experience. This study aims to develop SAC-assisted mathematics learning media and test its validity, practicality, and effectiveness in supporting the learning of flat-sided shapes. The study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of needs analysis, product design, media development, classroom implementation, and evaluation. The research instruments consisted of expert validation sheets for material and media, student questionnaires, and learning outcome tests. The validation process was carried out to assess the suitability of the content, appearance, and usefulness of the media, while the practicality and effectiveness tests were conducted through the use of media in classroom learning. The results showed that the SAC-based learning media achieved a highly valid rating from experts, was practical based on user responses, and was effective in increasing motivation and understanding of flat-sided spatial concepts. Thus, this media can be used as an alternative interactive learning resource that supports a more interesting, meaningful, and needs-based mathematics learning process for junior high school students.